Ethical and professionalism issues in dermatopathology: A cross‐sectional survey of American Society of Dermatopathology Members. (7th January 2021) - Brahmbhatt, Meera; Yeung, Howa; Vong, Gerard; Allbritton, Jill; Amin, Bijal; Dulaney, Eugene D.; Fullen, Douglas R.; LeBlanc, Robert E.; Ruben, Beth S.; Seykora, John T.; Vyas, Nikki S.; Stoff, Benjamin K.
Abstract: Background: Data regarding ethical/professional issues affecting dermatopathologists are lacking despite their importance in establishing policy priorities and educational content for dermatopathology. Methods: A 14‐item cross‐sectional survey about ethical/professional issues in dermatopathology was distributed over e‐mail to members of the American Society of Dermatopathology from June to September 2019. Results: Two hundred sixteen surveys were completed, with a response rate of 15.3%. Respondents ranked appropriate and fair utilization of healthcare resources (n = 83 or 38.6%) as the most often encountered ethical/professional issue. Conflict of interest was ranked as the most urgent or important ethical/professional issue (n = 83 or 39.3%). One hundred thirty‐three (61.6%) respondents felt "somewhat" or "not at all" well equipped to handle ethical dilemmas in practice and 47 (22.8%) respondents identified a major or extreme burden (eg, have considered resigning/retiring) due to ethical challenges. Conclusions: Areas of priority in ethics and professionalism issues can guide future policy and educational content in dermatopathology.